Acid-labile polysaccharide prodrug via lapatinib-sensitizing effect substantially prevented metastasis and postoperative recurrence of triple-negative breast cancer. Issue 25 (19th June 2020) - Sui, Junhui; Zhao, Mingda; Yang, Yuedi; Guo, Zhihao; Ma, Mengcheng; Xu, Zhiyi; Liang, Jie; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract : Co-delivery of lapatinib and Dox by polysaccharide prodrug prevented metastasis and recurrence of triple-negative breast cancer (TNBC) that is usually insensitive to endocrine and molecular targeted therapy. Abstract : Surgical resection and chemotherapy are routinely performed for triple-negative breast cancer (TNBC) because it is insensitive to endocrine therapy and molecular targeted therapy. Here, the optimal surface charge (−28 mV) and particle size (51 nm) enabled the acid-labile hyaluronic acid pullulan prodrug (HPP)-doxorubicin (Dox)/lapatinib (Lap) conjugate to circulate in the blood for a lengthy period of time and enhance the electron paramagnetic resonance effect, while the targeted molecule hyaluronic acid accelerated CD44 receptor-mediated 4T1 cell internalization. The inefficient anti-proliferation capability of Lap increased more than 10-fold after sensitization of Dox to metastatic 4T1 cells, while cellular uptake significantly increased, and cell viability dramatically decreased to nearly 20% of the free Dox group. Furthermore, HPP-Dox/Lap more effectively inhibited lateral mobility, vertical migration, and invasion ability of 4T1 cells. The ex vivo biodistribution of representative Dox indicated that Lap obviously facilitated the intratumoral infiltration and accumulation. The in vivo research revealed that there were overwhelming advantages in using HPP-Dox/Lap to inhibit tumor growth, progression, and lung metastasis even at a low dosage (1 mg kg −1 ), and it decreased postoperative recurrence and pulmonary metastatic nodules. Because of the excellent biosafety and visible therapeutic effect on the 4T1 metastasis and recurrence model, there is great potential value for HPP-Dox/Lap to be used to treat metastatic TNBC.